Transforming Discarded Mature Coconut Water into Carboxymethyl Cellulose as A Precursor Material for Bioplastics - Khusna Santika Rahmasari; Achmad Vandian Nur; Eka Anydia Putri; Vanesa Maharani; Achmad Ridlo; Bayu Ishartono (Science and Technology Indonesia, 2025)
(DMCW) mixture into the market’s drainage ditches after opening mature coconuts, resulting in soil contamination and odor due to acetic acid produced during fermentation by soil bacteria. This study aimed to minimize soil pollution caused by these activities through converting DMCW into versatile biopolymers such as carboxymethyl cellulose (CMC). The synthesis was initiated through the fermentation of DMCW into bacterial cellulose (BC) in the form of nata de coco (NdC), subsequently undergoing alkalization and carboxymethylation to produce CMC. The efficacy of the synthesis process from DMCW to CMC was identified via spectroscopy, thermal, and physicochemical analysis. The characterization results demonstrated that NdC-based CMC and commercial CMC exhibited analogous functional groups, diffraction patterns, thermal degradation behaviors, and physicochemical properties. NdCbased CMC revealed characteristics like water solubility, elevated molecular weight, and high viscosity, despite its purity being spproximately 83.3%. Notwithstanding its rigidity, lack of transparency, and water solubility, this NdC-based CMC can be solvent cast into bioplastics and degraded in soil in four days. In the future, CMC-based bioplastics, enhanced through advanced treatments, will be expected as precursors for the creation of sustainable food packaging materials